Randomised trials in maternal and perinatal health in low and middle-income countries from 2010 to 2019: a systematic scoping review - Joshua P Vogel; Jack Williams; Tari Turner; Steve McDonald; Alexander John Eggleston; Annabel Richards; Elise Farrington; Wai Chung Tse; Ayeshini Sella Hewage (BMJ Open)
Objectives To identify and map all trials in maternal health conducted in low and middle-income countries (LMIC) over the 10-year period from 2010 to 2019, to identify geographical and thematic trends, as well as comparing to global causes of maternal death and preidentified priority areas.Design Systematic scoping review.Primary and secondary outcome measures Extracted data included location, study characteristics and whether trials corresponded to causes of mortality and identified research priority topics.Results We searched the Cochrane Central Register of Controlled Trials database, a combined registry of trials from multiple sources. Our search identified 7269 articles, 874 of which were included for analysis. Between 2010 and 2019, maternal health trials conducted in LMICs more than doubled (50–114). Trials were conducted in 61 countries—231 trials (26.4%) were conducted in Iran. Only 225 trials (25.7%) were aligned with a cause of maternal mortality. Within these trials, pre-existing medical conditions, embolism, obstructed labour and sepsis were all under-represented when compared with number of maternal deaths globally. Large numbers of studies were conducted on priority topics such as labour and delivery, obstetric haemorrhage and antenatal care. Hypertensive disorders of pregnancy, diabetes and health systems and policy—despite being high-priority topics—had relatively few trials.Conclusion Despite trials conducted in LMICs increasing from 2010 to 2019, there were significant gaps in geographical distribution, alignment with causes of maternal mortality and known research priority topics. The research gaps identified provide guidance and insight for future research conduct in low-resource settings.Trial registration number 10.17605/OSF.IO/QUJP5.